2015
DOI: 10.18632/genesandcancer.69
|View full text |Cite
|
Sign up to set email alerts
|

Gene and miRNA expression changes in squamous cell carcinoma of larynx and hypopharynx

Abstract: Laryngo-pharyngeal squamous cell carcinomas are one of the most common head and neck cancers. Despite the presence of a large body of information, molecular biomarkers are not currently used in the diagnosis, treatment and management of patients for this group of cancer. Here, we have profiled expression of genes and microRNAs of larynx and hypopharynx tumors using high-throughput sequencing experiments. We found that matrix metalloproteinases along with SCEL, CRNN, KRT4, SPINK5, and TGM3 among others have sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…We previously identified a single nucleotide mutation of SCEL gene in both normal and squamous cell carcinoma of esophagus in African-Americans [52]. In our present study, SCEL is significantly under-expressed in African-American ESCC, and thus could play a role in squamous cell carcinogenesis as suggested by the down-regulation of this gene in larynx and hypopharynx [53], and in tongue squamous cell carcinoma [54]. …”
Section: Discussionsupporting
confidence: 52%
“…We previously identified a single nucleotide mutation of SCEL gene in both normal and squamous cell carcinoma of esophagus in African-Americans [52]. In our present study, SCEL is significantly under-expressed in African-American ESCC, and thus could play a role in squamous cell carcinogenesis as suggested by the down-regulation of this gene in larynx and hypopharynx [53], and in tongue squamous cell carcinoma [54]. …”
Section: Discussionsupporting
confidence: 52%
“…25 miRNA-CHIP assays has indicated that many miRNAs were aberrantly expressed in CRC. 26 Several steps were involved in the biogenesis of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…SCEL was enriched in stratified epithelia, where they play an important role in stress-bearing and barrier properties (8)(9)(10). Intriguingly, aberrant SCEL expression was elevated in varied malignant tumors including pancreatic cancer, colorectal cancer, and renal cancer [14][15][16] . However, it is largely unknown regarding the pathological role of SCEL in the development of GBC.…”
Section: Introductionmentioning
confidence: 99%